Ultrasound-assisted fractional precipitation of paclitaxel from Taxus chinensis cell cultures. (December 2019) - Seo, Hye-Won; Kim, Jin-Hyun
Graphical abstract: Highlights: Ultrasound-assisted fractional precipitation of paclitaxel was developed. Higher precipitation rate was found with ultrasound treated solutions. Precipitation time was dramatically shortened. The kinetics data agreed well with the Johnson-Mehl-Avrami-Komolgorov model. Abstract: In this study, we developed an ultrasound-assisted fractional precipitation for the purification of poorly water-soluble anticancer agent paclitaxel. The effects of ultrasound power (80, 180, 250, and 380 W) were investigated in samples of different purity (20.4, 63.6, and 92.7%) for precipitation. Higher precipitation rate and shorter precipitation time were found with ultrasound treated solutions than with those without ultrasound. When the experimental data were applied to the Johnson-Mehl-Avrami-Komolgorov (JMAK) equation, the rate constant increased to 200–500-fold for 20.4% of sample purity, 150–250-fold for 63.6% of sample purity, and 60–120-fold for 92.7% of sample purity by treatment with ultrasound. In addition, the lower the purity of the sample, the greater was the decrease in activation energy compared with the control, which means that the lower the sample purity, the more effective the fractional precipitation using ultrasound.